Critique to Early Shi‘ite Views on the ‘Uthmānī Muṣḥaf: Al-Bāqilānī’s Perspective - Darojat, Much Hasan; Hamat, Mohd Fauzi; Wan Ramli, Wan Adli (Jurnal Usuluddin, 2017)
This article aims to delineate al-Bāqilānī’s responses to the issues of the unauthenticity of the ‘Uthmānī Muṣḥaf claimed by the early Twelver Shi‘ites. As an Ash‘arite, he disproved their claims on the related topics; the status of the ‘Uthmānī Muṣḥaf and the Shi‘ite views on the muṣḥaf of the Qur’ān, and the integrity of the companions of the Prophet (peace be upon him). His arguments are also relevant to adress some Orientalists’ notions on the history of the Qur’ān which are in line with the Shi‘ites’ notion. His attempt obviously shows his capacity to maintain the mainstream of Sunnite theological framework. In this study, the approach that has been applied is textual analysis, using descriptive and analytical methods to investigate and analyze primary sources related to the issues. It also adopts the historical method to scrutinize several events on the subject.